Studi Komparasi Mediasi dan Konsiliasi Dalam Penyelesaian Sengketa Pada Korporasi - Hermawati, Mutiara; Rinanti, Pitra; Marito, Eugina Evita; Loren, Medina; Febriani, Anggie (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In the corporate world, disputes between parties often require efficient resolution methods outside of litigation. Two commonly used mechanisms are mediation and conciliation. Although both fall under alternative dispute resolution (ADR), they differ fundamentally, particularly in the role of the third party. A mediator remains neutral and facilitates negotiation without offering solutions, while a conciliator takes a more active role by providing written proposals to the parties. This article explores the differences, similarities, and legal basis of both mechanisms to offer clearer understanding for business actors in choosing the most suitable resolution method.